Kajian Normatif Lembaga Pemasyarakatan Padat Huni agar Warga Binaan menjadi Lebih Sehat dan Produktif sesuai Undang-Undang Nomor 12 Tahun 1995 tentang Pemasyarakatan - Heman Jasher. P; Jeane Neltje Saly (Jurnal Syntax Transformation, 2023)
This thesis normatively examines Correctional Institutions that exceed their capacity by optimizing coaching and a healthy lifestyle that does not neglect the Human Rights, Business, Health and Digital aspects by using the economic principles of Professor Richard Allan Posner, Inmates who are mentally and psychologically healthy will easy to benefit from entrepreneurship coaching and training so as to make Human Resources better. It seems that the government has not been able to maintain proper capacity prisons accompanied by maximum guidance even though it has built prison buildings. This can be seen from the tendency of former convicts to repeat wrongdoing and re-enter the correctional institution. Relevant agencies, in this case law enforcers, need to integrate technical support for Correctional Institutions so that the Prisoners become physically and mentally healthy and productive, for example the Police, the Prosecutor's Office as well as the Courts with their role in supporting so that the prison capacity is livable of course by not forcing to process or ensnare, prosecute someone in cases where the criminal facts are not strong. Densely inhabited Correctional Institutions as a formulation of the problem are ensuring that inmates are able to make them healthier and more productive, ensuring that the lifestyle of the inmates prioritizes physical and mental health, ensuring coaching and work training accompanied by a healthy environment can make the personality of the inmates better in the future when he returned to live in the midst of society. Today's Industry 4.0 era is the time to technically support Correctional Institutions so that Prisoners in their activities will be digitally monitored in addition to the availability of surveillance cameras in every corner and finger scans when passing through various rooms so that 24-hour activities can be seen which will produce a digital recap which can be used as material for assessment or credit points for Prisoners to obtain additional remissions, Prisoners also have the opportunity to work outside the Penitentiary to develop their entrepreneurial understanding, have indirectly taken part in supporting industry 4.0. Furthermore, Prisoners who are free can certainly develop their skills in the community.